ENTREPRENEURSHIP ORIENTATION AND BUSINESS PERFORMANCE: THE ROLE OF GOVERNMENT SUPPORT AS MODERATION (In Gen Z as Culinary Serving MSME Actors in Padang City) - Saputra, syailendra Eka; Lukman, Syukri; Hamidi, Masyhuri; Rahim, Rida; Adrianto, Fajri (JURNAL ECONOMICA : Research of Economic And Economic Education, 2024)
This study aims to empirically prove the effect of entrepreneurial orientation and government support on culinary MSME business performance in Padang City. In addition, this research also aims to prove the role of government support to strengthen the relationship between entrepreneurial orientation and culinary MSME business performance in Padang City. In this research, as many as 120 culinary actors managed by gen Z or business actors aged between 16 and 23 years were used at this time. Data collection was carried out through distributing questionnaires. The data analysis method used is quantitative by using path analysis. The results of testing the hypothesis found that entrepreneurial orientation will encourage increased culinary MSME business performance managed by gen Z in Padang City. The research results obtained also found that government support in the form of financial or non-financial has a strong influence on the performance of micro business businesses managed by gen Z in Padang City. Another finding obtained through our research is that government support moderates the relationship between entrepreneurial orientation and business performance. These findings show that the implementation of an entrepreneurial orientation will be carried out and on target if it gets financial or non-financial support from the government so that it can encourage increased business performance.